Is There an Association Between Self-Reported Dual-Task Performance and Fear of Falling in Older Adults? - Kartal Özcan, Ecem; Karabulut, Mustafa; Karakoç, Kürşad; Müjdeci, Banu (Journal of Aging & Physical Activity, 2024)
Introduction: Is there an association between self-reported dual-task performance and fear of falling in older adults? Background/Objectives: Fear of falling tends to increase with age and can negatively impact dual-task abilities, leading to potential declines in overall quality of life. Therefore, it becomes crucial to evaluate dual-task performance in older adults, particularly prior to the onset of fear of falling. This study aims to investigate the potential association between self-reported dual-task performance and fear of falling in older adults. Methods: A total of 51 individuals (19 females and 32 males) were recruited. The participants met the inclusion criteria were administered the Dual-Task Questionnaire (DTQ), Falls Efficiency Scale International, and Physical Activity Scale for the Elderly. Multiple linear regression was performed to predict DTQ scores based on age, body mass index, and Physical Activity Scale for the Elderly. Results: A moderate positive correlation was found between Falls Efficiency Scale International scores and self-reported DTQ scores (r:.448, p:.001). Age, body mass index, and Physical Activity Scale for the Elderly were not found to be significant predictors of DTQ scores. Conclusions: Our study reveals a moderate positive association between fear of falling and self-reported dual-task performance in older adults. A direct relationship between physical activity performance, fear of falling, and self-reported dual-task performance was observed among older adults. Significance/Implications: Integrating self-reported measures like the DTQ in clinical evaluations can provide valuable insights into dual-task abilities of older adults.